Regulation of MYC activity by post-translational modifications - Qiao, Xi (My University, 2018)
MYC is a transcription factor that is often found deregulated in cancer. Post-translational modifications, including phosphorylation and ubiquitination, play important role in controlling MYC expression and activity. This thesis investigates the in vivo effect of the cancerous inhibitor of protein phosphatase 2A (CIP2A)-regulated phosphorylation of MYC. Here, I find that phosphorylation of MYC at serine 62 (pS62MYC) recruits MYC to Lamin A/C-associated structures. In mouse model, CIP2A-mediated phosphorylation of MYC at S62 is connected to MYC-dependent initiation of proliferation, and support of intestinal regeneration in response to DNA damage. The study also identified ubiquitin protein ligase E3 component nrecognin 5 (UBR5) as a novel E3 ligase for MYC. UBR5 promotes MYC degradation by ubiquitination. Functionally, UBR5 defines MYC-dependent phenotypes both in normal and in cancer cells. In drosophila, inhibition of UBR5/HYD causes MYC-overgrowth of wing imaginal discs. In cancer cells, UBR5 keeps MYC expression level below the apoptotic priming threshold. Taken together, these results give us further understanding of the role of post-translational modifications in regulating MYC activity in normal tissue growth and regeneration, as well as in cancer.

Post-translationaaliset modifikaatiot transkriptiotekijä MYC:in aktiivisuuden säätelyssä MYC on transkriptiotekijä. Tietyillä post-translationaalisilla modifikaatioilla,kuten fosforylaatiolla ja ubikitinylaatiolla on tärkeä rooli MYC:in ilmentymisen ja aktiivisuuden säätelyssä. Tässä väitöskirjatyössä tutkittiin CIP2A-välitteisen MYC-fosforylaation in vivovaikutuksia. Havaitsimme että MYC proteiniissa oleva seriini62 aminohapon fosforylaatio aikaansaa MYC:in kulkeutumisen tumakalvon lamiini A/C:ta sisältäviin rakenteisiin sekä soluviljelmissä että hiiren kudoksissa. Hiirimallissa CIP2A:n todettiin olevan välttämätön DNA-vaurion jälkeiselle MYC seriini-62:n fosforylaatiolle, joka puolestaan tarvittiin suolipoimujen solujen jakautumiseen sekä suolen epitteelin uudistumiseen. Tässä tutkimuksessa tehtiin myös uusi havainto siitä, että UBR5 toimii E3-ligaasina MYC:lle ja edistää MYC proteiinin hajoamista. UBR5 määrittää MYC-riippuvaisia fenotyyppejä sekä normaaleissa soluissa että syöpäsoluissa. Banaanikärpäsessä UBR5/ HYD-inhibitio aiheuttaa MYC:in välityksellä siipien imaginaalilevyjen epänormaalia kasvua in vivo. Syöpäsoluissa UBR5 säätelee MYC:in ilmentymistasoa siten, että solut eivät joudu apoptoosiin. Saadut tulokset lisäävät ymmärrystämme post-translationaalisten modifikaatioiden merkityksestä MYC:in aktiivisuuteen normaalien kudosten kasvussa ja syövässä.